Crooning 1936–1956: the film musicals of Tino Rossi and Georges Guétary. Issue 3 (1st October 2020) - Powrie, Phil; Cadalanu, Marie
ABSTRACT: Many popular singers made film musicals in the period 1930–1960. This article focuses on two of the most popular and well-known chanteurs de charme in France, Tino Rossi and Georges Guétary, neither of whom has had academic work devoted to him. The article reviews their major films and their themes, and contrasts their reception and performance styles, arguing that they may well be seen in a relatively undifferentiated way, but that this disregards a shift in performance styles that is anchored in pre-war and post-war sensibilities.